Dynamic supply chain: A study in oil and gas industry - Saad, Shatina; Mohamed Udin, Zulkifli (2012)
The motivation of this study is to understand the environment of dynamic supply chain on oil and gas industry in Malaysia by looking into the dynamic supply chain capabilities and dynamic supply chain performance. Oil and gas enterprise-wide optimization span a large spectrum in a supply chain, from the strategic to the tactical to the operational level and other various functions in the supply chain network, from purchasing of the raw materials through the refinery activities to the distribution and sales.Integrated and coordinated decision making across various geographically distributed refinery activities and storage sites also offers additional challenges to refinery operations optimization.While refinery facilities management is an integral part of enterprise-wide optimization, transportation logistics and finished product distribution management remain important parts of the oil and gas supply chain. Although, technical advancement and time were the core values aiming only for fast exploration and higher production of oil and gas, supply chain in the oil and gas industry can either make or break the project if careful attention and precautions are not taken seriously by players in an industry.Increasing economic volatility has severely disrupted the supply chains of companies across industries. Rapid swings in the availability and price of key commodities, major currency fluctuations, disturbance in financial markets, disruptive geopolitical events and continued development of customer channels on a global basis have conspired to place unique pressure on the way these companies source, manufacture and distribute products.Therefore, this study is to identify and understand the dynamic supply chain capabilities and dynamic supply chain performance as a whole perspective of dynamic supply chain on the oil and gas industry practices. Specifically, the dynamic supply chain capabilities and dynamic supply chain performance will be discussed in this study are the firm's capabilities in the dynamic supply chain of oil and gas industry.